Cardiac Resynchronization Therapy in Anomalous Coronary Sinus: A Case Report (Bangladesh Heart Journal, 2023)
A 37-year-old man, a known case of Dilated Cardiomyopathy (DCM) with Post PPM (Permanent Pacemaker) status for last 3 years underwent upgrading of PPM to Cardiac Resynchronization Therapy Pacemaker (CRT-P) in a specialized cardiac center. During the implantation procedure, there was anomalous branching of coronary sinus with absence of lateral branch & presence of a highly tortuous posterior branch causing difficulty in lead placement. Finally left ventricular (LV) lead was placed in the tortuous branch using Judkin’s right catheter. Lead position was stable with excellent threshold. The patient has been followed up with improvement of symptoms.Bangladesh Heart Journal 2023; 38(2): 155-157